Knowledge and attitudes about end-of-life decisions, good death and principles of medical ethics among doctors in tertiary care hospitals in Sri Lanka: a cross-sectional study - Chang, Thashi (BMC Med Ethics, 2021)
BACKGROUND: Competent end-of-life care is an essential component of total health care provision, but evidence suggests that it is often deficient. This study aimed to evaluate the knowledge and attitudes about key end-of-life issues and principles of good death among doctors in clinical settings. METHODS: A cross-sectional study was conducted among allopathic medical doctors working in in-ward clinical settings of tertiary care hospitals in Sri Lanka using a self-administered questionnaire with open- and close-ended questions as well as hypothetical clinical scenarios. Univariate and logistic regression analysis were used to identify the independent factors associated with knowledge and attitudes. RESULTS: Of the responders who had not been a caregiver for a terminally ill relative (n = 390), 57.9% were men with a mean age of 36.5 years (SD = 8.2). Compared to undergraduate (65.6%; n = 256), only 27.4% (n = 107) had received end-of-life care training at postgraduate level. Only 65.9% of doctors favoured disclosing terminal prognosis to patients; 27.7% of doctors were aware of advance directives; 14.6% were aware of the correct time of death when certifying brain death; 70.3% felt more comfortable in withholding than withdrawing life-sustaining treatment; 61.3% were aware of do-not-attempt cardiopulmonary resuscitation (DNACPR) decisions while 26.7% felt reluctant to administer it; 15.1% thought that all life-sustaining therapy should be withdrawn with a DNACPR decision; and only17.9% were able to name the four principles of medical ethics while 57.9% could not name a single. Participants scored a mean of 9.2 (SD = 3.9) of a maximum 14 points when tested on principles of a ‘good death’. Doctors who had pursued postgraduate studies were more likely to be aware of breaking bad news (adjusted-Odds-Ratio:1.99; 95%CI = 1.19–3.32), advance directives (adjusted-OR: 4.15; 95%CI = 2.49–6.94), aware of certifying the correct time of death (adjusted-OR:2.37; 95%CI = 1.33–4.2) and less reluctant to make DNACPR decisions (adjusted-OR:1.74; 95%CI = 1.13–2.68). Doctors who had worked in ICU were more comfortable withholding than withdrawing treatment (adjusted-OR:1.99; 95%CI = 1.2–3.31). CONCLUSIONS: Knowledge and attitudes about end-of-life care, good death and principles of medical ethics among doctors in Sri Lanka were suboptimal. Structured training of end-of-life care needs to be integrated within curricula and in-service training. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12910-021-00631-5.